Ostracodal evolution during the Permian–Triassic transition at the Youping section of the Nanpanjiang Basin - Ji, Xia; Huang, Yunfei; Sun, Xin; Qiu, Xincheng; Yang, Hao; Tong, Jinnan; Yi, Xuefei; Tian, Li (Frontiers in Ecology and Evolution, 2023)
The Permian-Triassic mass extinction has been considered the largest bio-crisis since the Phanerozoic, with more than 90% of marine taxa extinct. Previous studies showed that ostracods suffered various extinction patterns in different localities and were relatively enriched in the lowermost Triassic shallow marine microbialites. Multiple hypotheses have been put forward to explore the reasons for this phenomenon. Abundant ostracod fossils were collected from the microbialite-bearing Youping section in the Nanpanjiang Basin. 45 species in 22 genera from Wujiaping Formation increased dramatically to 104 species in 33 genera from the microbialites of basal Luolou Formation. However, Ostracods from the Youping section suffered severe extinction during the second phase of the Permian-Triassic crisis, i.e., the earliest Triassic mass extinction (ETME), rather than the first phase, i.e., the latest Permian mass extinction (LPEM). In addition, the Sørenson coefficient has been used to examine the similarity of faunal associations among different sections of the same beds. Ostracods showed remarkable geographical differentiation at both regional and global scales during the Permian-Triassic transitional beds and were presumably controlled by geographical isolation.